Spontaneous Coronary Artery Dissection and Implantation of Absorb Bioresorbable Drug-Eluting Stent in Cocaine-Related Acute Coronary Syndrome - Roberto Ceravolo; Marco Vatrano; Giuseppe Dattilo; Alessandro Ferraro; Vincenzo Antonio Ciconte; Egidio Imbalzano (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2014)
Introduction Spontaneous coronary artery dissection (SCAD) is a rare entity leading to acute coronary syndrome (ACS). Some of these reported cases have occurred in young patients who abuse cocaine that may produce coronary vasospasm, thrombotic coronary occlusion, and marked systemic hypertension. There is no standardized therapeutic management for patients with SCAD, as there are no studies comparing different strategy due to the small number of cases reported in the literature. To the best of our  knowledge, no data are available regarding the use of bioresorbable vascular scaffold (BVS) stent in patients with ACS due to coronary artery dissection secondary to cocaine abuse. Case History A 27-year-old male presented to the emergency department with residual chest pain began two days before. He was current smoker with family history of coronary artery disease. In addition, he reported fever in the previous week. His electrocardiogram revealed negative precordial T-wave and echocardiogram showed a hypokinetic anterior wall with reduced left ventricular function. Highsensitive troponin-T (hs Tn-T) and Creatine Kinase (CK) levels were increased. Due to patient's clinical status and to the instrumental and laboratory findings he was referred to our cardiologic department. At admission, the patient was hemodinamically stable (heart rate: 70 bpm; blood pressure: 130/80 mm Hg) and fully asymptomatic. Physical examination was within normal parameters. Considered clinical presentation suggesting acute myocarditis, it was decided to manage the patient conservatively.